Un protagonismo recobrado la Democracia Cristiana chilena y sus vínculos internacionales (1973-1990) - Ulianova, Olga (Ariadna Ediciones, 2021)
The Christian Democratic Party has been a key piece in the more general insertion of Chilean politics in the great political-ideological trends that dominated the second half of the 20th century. During the past century, relations between external and Chilean political actors were framed in the context of great processes and dilemmas of global relevance: the Cold War and the more general competition between holistic social projects, the emerging concern for human rights, the experience of post-dictatorial transitions in Southern Europe, among others. These external actors played a very relevant role in promoting the political exit strategy from the Chilean dictatorship which, by converging with internal factors, had an important impact in determining the guidelines of the transition. Local political actors, such as the PDC, far from being pieces in the hands of external referents, played a leading role, using their international networks to consolidate and consolidate their political project. Unlike other works that have addressed the international dimension of the transition, the focus of this book is not the economic or the ideological aspects, but rather the political centrality of an actor, the Christian Democratic Party, and the capacity that it it had to consolidate at the international level its position of reference for the return to democracy in Chile.